The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5539/ass.v8n10p8
|View full text |Cite
|
Sign up to set email alerts
|

Organ Donation among Malaysian: The Malay Dilemma toward Social Development

Abstract: Organ donation among the world community today is not a new phenomenon. The noble act of organ donation by donors that at times, has no blood relations has enabled many patients with chronic diseases to earn a second chance in life. The same scenario also takes place in Malaysia in which awareness of organ donation to help parties in need is not new. Many citizen of Malaysia is aware that their contribution gives "new life" to the needy. This little "scarifies" indirectly shows that Malaysian people put a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Furthermore, most Malays refused to donate a kidney due to the lack of transparent disclosure or discussion on this issue [17]. This finding concurs with national reports that show Malays donated organs the least among the three main ethnicities [3].…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, most Malays refused to donate a kidney due to the lack of transparent disclosure or discussion on this issue [17]. This finding concurs with national reports that show Malays donated organs the least among the three main ethnicities [3].…”
Section: Discussionsupporting
confidence: 80%
“…A study on organ donation in Malaysia reported that Malay and Muslim were unsure or unwilling to donate their organs as compared to Chinese and Buddhist (Abidin et al, 2013). The Malays face the dilemma of being sceptical of whether their religion permits them to make organ donations (Noordin et al, 2012). As the majority of students were Malay (96.5%) and Muslim (97.7%) in this study, it was quite challenging to justify whether the same scenario applies to tooth donation as there was a small number of students representing other ethnicities (3.5%) and religion (2.3%).…”
Section: Discussionmentioning
confidence: 82%
“…10,11 Another evidence of traditional cultural values influencing people's decision to donate tissue/organs is the statistics obtained from 2000 to 2010 by National Transplant Resource Centre, Kuala Lumpur, which reported that donation among the Malay community (the dominant ethnic group in Malaysia) contributed to only 6.36% of the total organ donation as compared to 61.86% by Chinese and 31.78% by Indians; the study cited the Malay community's perception that their religion, Islam, did not permit them to donate tissue/organs as the primary reason for their low donation rates. 12 Thirdly, although most healthcare professionals support tissue donation, not many of them have registered to pledge for tissue donation. This attitude of healthcare professionals may be attributed to several reasons: 1) lack of awareness that tissue donation is by opt-in system (MTERA), and not an opt-out system (HOTA) for organs; 2) lack of information about what is required of them to join the registry; and 3) signing up as a pledger is not a priority.…”
Section: Discussionmentioning
confidence: 99%